"Thank You for Giving Me a Voice!" A Longitudinal Evaluation of Patients' Experience of Partnering With Students in an Australian Medical School. (9th March 2017) - Ivory, Kimberley Dale; Luscombe, Georgina; Klein, Linda Ann; Barratt, Alexandra
Background: We evaluated the patient-partner experience in a longitudinal program called Integrated Population Medicine in the Sydney Medical School to assess its acceptability. The program exposed senior medical students to the lived experience of chronic disease. Methods: We surveyed 267 people with chronic conditions recruited as patient-partners by the 2012 student cohort in a mixed-methods longitudinal cohort study. Surveys were administered 'over' 18 months: before, during, and after the program. Results: A total of 155 (58%) patient-partners completed the baseline survey; 52 patients returned all 3 surveys. Patient-partners remained very positive about the program across all surveys. More than 95% of respondents enjoyed interacting with the student, and most were very positive about their role in teaching the student. Three major themes emerged: willingness to help, a sense of gratitude and enjoyment, and a chance to teach and learn. Participants were willing to discuss their illness experiences and were keen to spend more time with students. Conclusions: Patients are willing participants in longitudinal patient-partner programs. They perceive benefits for themselves and others, for the health system, and for students and would like to become more actively involved in medical education.